(3GdeDJda hGdeNJda ef GdCSeGA aj GdMOjKs - (3GHf GdbjSQGfj , eMeO Hf WGgQ Hf eMeO GdebOSj, CHh GdaVd,J (B507 (3g` s ((3eMeO Hf GdMGL YHO Gddg Hf eMeO GdeYQha LOg HGHf eaQL GdeYXeGfi GdOeTbi s)
(3ChdgG (B:s
(3GdMeO ddg hHg CSJYjf hUdhGJg Ydi QShdg hBdg hUMHg CLeYjf s
(3BNQgG (B:s
(3BNQ GdKGdK ef GdCUd hgh BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B85 - (3U(B115s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B171 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B98s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B163 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI HOeTb (B((3JUha (B129) s
Keywords: (3GdJGQjNs